Pentadinium dababiyaense: A new organic-walled dinoflagellate cyst from the Upper Cretaceous, Dababiya, Egypt. (January 2019) - Soliman, Ali; Slimani, Hamid
Abstract: Pentadinium dababiyaense is a new, organic-walled dinoflagellate cyst (dinocyst), described herein from Upper Cretaceous core material from the Dababiya borehole, Upper Nile Valley, Egypt. It is characterized by having a distinctive cavate apical horn and cavate sutural crests with lace-like perforations in the periphragm. The sutural crests, together with the precingular type P archeopyle indicate a gonyaulacoid tabulation. The species has a very short stratigraphic range within the latest Maastrichtian and may constitute a useful stratigraphic marker. Highlights: A new dinocyst, Pentadinium dababiyaense is described. It has a cavate apical horn and cavate sutural crests with lace-like perforations. It has a very short stratigraphic range in the latest Maastrichtian.